2007
DOI: 10.1603/0022-2585(2007)44[150:eotomo]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Temperature on Metabolism of <I>Phlebotomus papatasi</I> (Diptera: Psychodidae)

Abstract: Phlebotomus papatasi (Scopoli) (Diptera: Psychodidae) is the most important vector of Leishmania major, and previous experiments revealed that Leishmania development in the sand fly midgut is significantly affected by temperature. Therefore, we maintained blood-fed P. papatasi females at 23 or 28 degrees C to understand the effect of temperature on bloodmeal digestion and developmental times of this sand fly. At the lower temperature, the metabolic processes were slower and developmental times were longer: def… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
36
0
3

Year Published

2008
2008
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 62 publications
(46 citation statements)
references
References 13 publications
5
36
0
3
Order By: Relevance
“…Temperature and relative humidity were shown to play important roles in the transmission by influencing vector survival, parasite development rate and sandfly feeding behaviour (WHO 2000, Benkova & Volf 2007, Dinesh et al 2008. Our study indicates that indoor relative humidity and temperature are highly associated with increased risk for P. argentipes breeding and leishmaniasis infection.…”
Section: Discussionmentioning
confidence: 70%
“…Temperature and relative humidity were shown to play important roles in the transmission by influencing vector survival, parasite development rate and sandfly feeding behaviour (WHO 2000, Benkova & Volf 2007, Dinesh et al 2008. Our study indicates that indoor relative humidity and temperature are highly associated with increased risk for P. argentipes breeding and leishmaniasis infection.…”
Section: Discussionmentioning
confidence: 70%
“…Sand flies have quite eclectic eating habits, such that they seek to circulate between animal shelters and human dwellings, between the peridomicile and the sylvatic environment. The females are non-autogenous and require blood meals for oviposition and to complete the life cycle 23 . They only require feeding on blood a few times in their lives, and thus, like males, use plant sap and nectar as their main sources of energy and water 24 .…”
Section: The Available Hypotheses or Explanations For The Urbanizatiomentioning
confidence: 99%
“…Moreover, the incubation period of pathogens inside vectors tends to be shorter at warmer temperatures. Previous studies showed that temperature affects significantly the density and dynamics of Phlebotomus papatasi [21][22][23][24]. The work of Kassem et al [25] in the Nile Delta revealed that sand fly densities were strongly correlated to temperature but not to relative humidity or wind velocity.…”
Section: Discussionmentioning
confidence: 99%